MATHEMATICAL MODEL FOR SOFTWARE USABILITY AUTOMATED EVALUATION AND ASSURANCE - І. Гученко (Vìsnik Nacìonalʹnogo Avìacìjnogo Unìversitetu, 2011)
The subject of the research is software usability and the aim is construction of mathematical model of estimation and providing of the set level of usability. Methodology of structural analysis, methods of multicriterion optimization and theory of making decision, method of convolution, scientific methods of analysis and analogies is used in the research. The result of executed work is the model for software usability automated evaluation and assurance that allows not only to estimate the current level of usability during every iteration of agile development but also to manage the usability of created software products. Results can be used for the construction of automated support systems of management the software usability.